USE OF TRADITIONAL TYPES OF MEDICINAL PLANTS IN EAST ROTE DISTRICT, ROTE NDAO DISTRICT - Aprilia Ballo; Sonya T. Nge (Jurnal Penelitian Pendidikan IPA, 2025)
The community in East Rote District continues to rely on a variety of natural plants for traditional medicine purposes. This study aims to identify the types of medicinal plants used, their functions, and the methods of preparation and application among residents. A descriptive method with an exploratory survey technique was employed during the research, which was conducted from November to December 2024. The findings are that traditional medicinal knowledge remains prevalent, with 38 distinct plant species utilized by the community. These plants are used to treat a wide range of ailments, including hematemesis, surgical wounds, low back pain, incisions, canker sores, chickenpox, gastric disorders, coughs, back pain, bleeding, boils, fever, diarrhea, ulcers, headaches, rheumatism, hepatitis, malaria, colds, toothaches, high fever, body odor, cancer, asthma, internal illnesses, diabetes, respiratory infections, hypertension, complications during childbirth (especially placental expulsion), and internal heat. Among the plant parts used, leaves are the most commonly used. The primary methods of processing include boiling, direct consumption, topical application, pounding, and burning. These findings highlight the enduring significance of ethno botanical knowledge in the health practices of the East Rote community and underscore the need for documentation and conservation of traditional medicinal practices.